2020
DOI: 10.1017/wsc.2020.92
|View full text |Cite
|
Sign up to set email alerts
|

An integrated weed management strategy for the control of horseweed (Conyza canadensis)

Abstract: Multiple herbicide-resistant populations of horseweed [Conyza canadensis (L.) Cronquist] continue to spread rapidly throughout Ontario, notably in areas where no-till soybean [Glycine max (L.) Merr.] is grown. The occurrence of multiple herbicide resistance within these populations suggests that the future role of herbicide tank mixtures as a means of control will be limited. An integrated weed management strategy utilizing complementary selection pressures is needed to reduce the selection intensity of relyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Other studies measuring impact of vertical tillage on crop yield report varying results. In one study, vertical tillage increased soybean yield (Watters & Douridas, 2013), while another study reported increases in corn yield after vertical tillage but not soybean yield (Van Dee, 2005). Several cooperating farms within this study have invested in planter technologies, such as automatic and pneumatic adjustment of row-unit down pressure and closing wheel systems of various types.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies measuring impact of vertical tillage on crop yield report varying results. In one study, vertical tillage increased soybean yield (Watters & Douridas, 2013), while another study reported increases in corn yield after vertical tillage but not soybean yield (Van Dee, 2005). Several cooperating farms within this study have invested in planter technologies, such as automatic and pneumatic adjustment of row-unit down pressure and closing wheel systems of various types.…”
Section: Discussionmentioning
confidence: 94%
“…Trends from a small body of research suggest that vertical tillage may improve crop performance, including crop stand establishment and crop yield (Van Dee, 2005;Watters & Douridas, 2013). Many growers use vertical tillage tools to create a warming and drying effect on soil conditions to achieve timelier planting and more even crop emergence and establishment in high-residue environments.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Tillage, though, has a major role in a reduction in seed germination and may be associated with reduced herbicide rates to achieve a high control of weeds. For instance, the application of 350 g ae ha −1 of 2,4-D ester in horseweed (Conyza canadensis) provided equal control in terms of weed biomass and density reduction compared to higher doses of 2,4-D (600 or 850 g ae ha −1 ) in spring sprayings after shallow fall tillage [92]. However, it should be noted that reduced sublethal herbicide rates might cause crop phytotoxicity and yield reductions, as indicated by research regarding the effects of sublethal rates of synthetic auxin herbicides in soybean production [93].…”
Section: Reducing Weed Pressure With "Smart" Cultivation Techniquesmentioning
confidence: 99%